Item Analysis of Multiple Choice Questions (MCQs) for Dangerous Goods Courses in Air Transportation Management Department - Suryono, Wiwid; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
Analysis of question items is an assessment of the questions that are evaluated to measure quality. Analysis of question items has two ways, namely quantitative and qualitative question item analysis. The goal to be achieved is to find out the quality of the multiple-choice form of Final Semester Exam questions and also to detect sound and wrong questions. The method used in this study is the quantitative descriptive method. Data collection uses documentation, interviews, and observations. The Excel program uses data analysis to detect the quality of good and bad questions. The results of the quantitative analysis of the reliability of multiple-choice questions of 0.76 mean reliable questions. Difficulty index: 3 medium questions (6%), 47 easy questions (76%), and 9 very easy questions (18%). Discrimination index: 8 questions are very low (16%), 22 questions are low (44%), 9 questions are medium (18%), and t10 questions are high (20%). Distractor efficiency: 125 items of malfunctioning questions (83.33%) and 25 items of functioning questions (16.67%).